Structure of won medals, most successful teams, and wrestlers by continents at the Olympic Games 2024 - Slacanac, K.; Dokmanac, M. (International Journal of Wrestling Science, 2024)
Given these insights, there is a need for a detailed analysis of the technical and tactical actions of teams and individual wrestlers, including techniques, wrestling positions, time spent, and overall efficiency. This will help determine the true reasons behind the superior performance of Asian wrestlers compared to their European counterparts, particularly in terms of medal wins This paper defined the structure of medals won by continent, determined the structure of medals won by nation, and identified the best wrestlers by style. Japan, the United States of America, and the Islamic Republic of Iran were the most successful nations. Asian countries won 50% of all medals, while European wrestlers experienced a notable decline in the number of medals (27.77%) and their performance quality. In Greco-Roman wrestling (GR), lower WQ (points per minute), the total number of points scored, and points per match are observed than in Freestyle Wrestling (FS) and Women`s Wrestling (WW). This highlights the reduced efficiency and attractiveness of the GR style. Additionally, some nations granted citizenship to foreign wrestlers who subsequently won medals for them in these Olympic Games. The study also pointed out the extremely high efficiency among Japanese female wrestlers, in contrast to the low efficiency (only 16.67%) of European female wrestlers compared to GR and FS. This disparity indicates underdevelopment in women`s wrestling in Europe, highlighting areas for further research and improvement. A comprehensive performance analysis of teams and wrestlers is crucial, focusing on techniques, wrestling positions, timing, and overall efficiency. Such analysis could reveal the reasons behind the superior performance of Asian wrestlers compared to their European counterparts and help guide improvements.